Safety and efficacy of self‐administered romiplostim in patients with immune thrombocytopenia: Results of an integrated database of five clinical trials. Issue 6 (21st March 2020) - Kuter, David J.; Arnold, Donald M.; Rodeghiero, Francesco; Janssens, Ann; Selleslag, Dominik; Bird, Robert; Newland, Adrian; Mayer, Jiri; Wang, Kejia; Olie, Robert
Abstract: Romiplostim self‐administration by patients or caregivers may offer time/cost savings to healthcare professionals (HCPs) and convenience for patients who avoid weekly clinic visits. We performed an integrated analysis of five clinical trials to evaluate the efficacy and safety of romiplostim self‐administration. Data were analyzed from adults with immune thrombocytopenia (ITP) who received weekly romiplostim via self‐administration or from an HCP. Patients who achieved a stable romiplostim dose for ≥3 weeks (HCP group ≥5 weeks to provide an appropriate index date to enable comparisons with the self‐administration group) with platelet counts ≥50 × 10 9 /L were eligible. In the self‐administration (n = 621) vs HCP (n = 133) groups, respectively, median age was 53 vs 58 years, median time since primary ITP diagnosis was 3.7 vs 2.5 years, and median baseline platelet count at ITP diagnosis was 19.0 vs 20.0 × 10 9 /L. In the self‐administration and HCP‐dosed groups, median romiplostim treatment duration was 89 vs 52 weeks and median total number of doses was 81 vs 50, respectively. In the self‐administration and HCP groups, respectively: 95.0% and 100.0% of patients achieved ≥1 platelet response (defined as weekly platelet count ≥50 × 10 9 /L without rescue medication in previous 4 weeks); the median percentage of weeks with a response was 94.5% and 95.9%; and rescue medication was used in 36.7% and 39.8% of patients. Self‐administration did not adversely affect safety; duration‐adjusted rates for all treatment‐emergent adverse events (TEAEs) and bleeding TEAEs were numerically lower with self‐administration. Romiplostim self‐administration appears effective and well tolerated in eligible patients with ITP.